An insight into recent developments of copper, silver and gold carbon dots: cancer diagnostics and treatment - Ullah, Ihsan; Suliman, Hazrat; Alamzeb, Muhammad; Abid, Obaid-Ur-Rahman; Sohail, Muhammad; Ullah, Mohib; Haleem, Abdul; Omer, Muhammad (Frontiers in Bioengineering and Biotechnology, 2023)
Cancer is one of the most fatal diseases globally, however, advancement in the field of nanoscience specifically novel nanomaterials with nano-targeting of cancer cell lines has revolutionized cancer diagnosis and therapy and has thus attracted the attention of researchers of related fields. Carbon Dots (CDs) – C-based nanomaterials – have emerged as highly favorable candidates for simultaneous bioimaging and therapy during cancer nano-theranostics due to their exclusive innate FL and theranostic characteristics exhibited in different preclinical results. Recently, different transition metal-doped CDs have enhanced the effectiveness of CDs manifold in biomedical applications with minimum toxicity. The use of group-11 (Cu, Ag and Au) with CDs in this direction have recently gained the attention of researchers because of their encouraging results. This review summarizes the current developments of group-11 (Cu, Ag and Au) CDs for early diagnosis and therapy of cancer including their nanocomposites, nanohybrids and heterostructures etc. All The manuscript highlights imaging applications (FL, photoacoustic, MRI etc.) and therapeutic applications (phototherapy, photodynamic, multimodal etc.) of Cu-, Ag- and Au-doped CDs reported as nanotheranostic agents for cancer treatment. Sources of CDs and metals alogwith applications to give a comparative analysis have been given in the tabulated form at the end of manuscript. Further, future prospects and challenges have also been discussed.